Competitor presence reduces internal attentional focus and improves 16.1 km cycling time trial performance. Issue 4 (July 2015) - Williams, Emily L.; Jones, Hollie S.; Andy Sparks, S.; Marchant, David C.; Midgley, Adrian W.; Mc Naughton, Lars R.
Abstract Objectives Whilst the presence of a competitor has been found to improve performance, the mechanisms influencing the change in selected work rates during direct competition have been suggested but not specifically assessed. The aim was to investigate the physiological and psychological influences of a visual avatar competitor during a 16.1-km cycling time trial performance, using trained, competitive cyclists. Design Randomised cross-over design. Methods Fifteen male cyclists completed four 16.1 km cycling time trials on a cycle ergometer, performing two with a visual display of themselves as a simulated avatar (FAM and SELF), one with no visual display (DO), and one with themselves and an opponent as simulated avatars (COMP). Participants were informed the competitive avatar was a similar ability cyclist but it was actually a representation of their fastest previous performance. Results Increased performance times were evident during COMP (27.8 ± 2.0 min) compared to SELF (28.7 ± 1.9 min) and DO (28.4 ± 2.3 min). Greater power output, speed and heart rate were apparent during COMP trial than SELF (p < 0.05) and DO (p ≤ 0.06). There were no differences between SELF and DO. Ratings of perceived exertion were unchanged across all conditions. Internal attentional focus was significantly reduced during COMP trial (p < 0.05), suggesting reduced focused on internal sensations during an increase in performance. Conclusions Competitive cyclists performed significantly faster during a 16.1-km competitive trial than when performing maximally, without a competitor. The improvement in performance was elicited due to a greater external distraction, deterring perceived exertion.